Antioxidant System and its Functioning in Animal Organisms - R. Fatkullin, R; A. Ovchinnikov, A; M. Ermolova, E; V. Matrosova, Y; A. Chulichkova, S (International Journal of Engineering and Technology, 2018)
According to the opinion of F. Z. Meyerson, one of the main reasons for disruption of organs' plastic functions under stress is insufficient intake of substrates and cofactors required for synthesis of nucleic acids and protein, as well as partial or complete fasting. In the first stage, according to the author, activity of amino acidsâ€™ gluconeogenesis and transamination enzymes increases through the neurohumoral effect, which is the reason of reduced synthesis of protein and transformation of amino acids into glucose, i.e. plastic resources of the organism, its structural proteins, and energy resources in particular, are transformed.Â Â